Analisis Pelaksanaan Program Antenatal Terpadu pada Masa Pandemi COVID-19 di Puskesmas Tamamaung Kota Makassar - Nurdiana Nurdiana; Daswati Daswati; Mutia Rahmawati (Poltekkes Kemenkes Maluku, 2022)
Integrated antenatal care is a comprehensive and quality antenatal service provided to all pregnant women. The purpose of the study was to determine the implementation of the integrated antenatal program during the COVID-19 pandemic at the Tamamaung Health Center in Makassar City. Qualitative research method with four primary informants with purposive sampling technique and 11 triangulation informants. Data collection used in-depth interview guidelines, observation sheets, and documentation. The results of the study concluded that the input aspect of Human Resources was sufficient and by the standards of the Ministry of Health of the Republic of Indonesia. The facilities are adequate, but the building infrastructure requires room expansion because it is still small. Funding is available from BOK and BPJS. Policies and SOPs, as well as aspects of the process, are by the Integrated AntenatalGuidelines of the Indonesian Ministry of Health and Practical Instructions for Maternal and Newborn Health Services during the COVID 19 Pandemic. The output aspect has increased by sloping COVID-19 cases with K1 75% and K4 70%. It is hoped that the increase in integrated antenatal services so that the monitoring of pregnant women during the COVID-19 pandemic can run well.